Słupski eksperyment gospodarczy z lat osiemdziesiątych XX w. Między reformą a propagandą - Gryko, Arkadiusz (Komunizm: System - Ludzie - Dokumentacja, 2023)
Due to the interest of the central party authorities and the attention of the national media in the late 1980s, the Słupsk Voivodeship became a symbol of successful economic reforms. The Słupsk economic experiment was the outcome of programs aimed at intensifying agricultural production and housing development implemented in the voivodeship. Its creators were Czesław Przewoźnik, the voivode of Słupsk, and Zygmunt Czarzasty, the first secretary of the Polish United Workers’ Party’s Provincial Committee in Słupsk, who decided on such a response to the resolutions of the 10th Polish United Workers’ Party Congress in 1986. Congress’s resolutions declared the need to increase agricultural production and solve the housing problem, then the most critical social and economic problems of the country. The experiment was an attempt to improve the efficiency of the socialist economy, but it also served as the authors’ selfpromotion as their political aspirations went far beyond Słupsk. Propaganda-wise, the central party authorities used the Słupsk experiment on an even broader scale. When the effects of healing the economy as part of the second stage of economic reform were not visible, the authorities tried to prove that the socialist economy was still worth rebuilding, and, just as in Słupsk Voivodeship, it could produce results